The Impact of Lifestyle and Product Quality on Seulgi Doll Purchasing Decisions: A Case Study of PT Prima SH Indonesia - kamalia, Rahmadienna Fachrunnisa; Muis, Indra (Yayasan Ilomata, 2024)
The doll industry has experienced rapid growth, with Indonesia becoming the fourth-largest market globally in 2023. Seulgi dolls, a local product featuring diverse designs and good quality, present an interesting subject for research on the influence of lifestyle and product quality on purchasing decisions. This study aims to analyze the impact of lifestyle and product quality on Seulgi doll purchasing decisions, both separately and in interaction. The specific objectives are to determine the individual effects of lifestyle and product quality, as well as their combined contribution to doll purchasing decisions. This research employs a quantitative approach with a sample size of 100 respondents, using Non-Probability Sampling technique with Purposive Sampling method. Analysis results reveal that lifestyle has no significant effect on Seulgi doll purchasing decisions, with a significance 0.255>0.05. Product quality, however, proves to have a positive and significant impact on purchasing decisions, with a significance 0.000<0.05. These findings emphasize the importance of product quality in influencing Seulgi doll purchasing decisions, while consumer lifestyle is not a primary determinant. Both lifestyle and product quality simultaneously influence Seulgi doll purchasing decisions, as evidenced by the F-test significance. The F-value of 48.172 is also substantial, indicating that at least one predictor has a significant effect on the dependent variable. By enhancing Seulgi doll quality, maintaining reputation, responding to complaints, strengthening fan-based marketing strategies that highlight quality, and investigating other variables such as price and promotion that affect purchasing decisions, the company can increase Seulgi doll sales and maintain competitiveness in the market.